Role of CT in assessing pleural malignancy prior to thoracoscopy. - Hallifax, R; Haris, M; Corcoran, J; Leyakathalikhan, S; Brown, E; Srikantharaja, D; Manuel, A; Gleeson, F; Munavvar, M; Rahman, N (BMJ Publishing Group, 2014)
The definitive diagnosis of pleural malignancy depends upon histological confirmation by pleural biopsy. CT is reported to have a high sensitivity and specificity for the diagnosis of malignant pleural disease, and is part of the routine diagnostic workup of these patients. The aim of this study was to assess the sensitivity and specificity of CT in detecting pleural malignancy prior to definitive histology obtained via thoracoscopy in a large cohort of patients with suspected malignant pleural disease. Retrospective review of thoracoscopies between January 2008 and January 2013 at two UK tertiary referral centres: Oxford and Preston. The histological results were compared with the CT reported diagnosis before the procedure. CT scan reports were assessed by independent respiratory physicians as to whether the radiologist concluded evidence of malignant pleural disease or benign features only. 211 (57%) of 370 patients included in the analysis had malignant disease: CT scans were reported as 'malignant' in 144, giving a sensitivity of 68% (95% CI 62% to 75%). Of the 159 patients with benign disease, 124 had CT scans reported as benign: specificity 78% (72% to 84%). The positive predictive value of a malignant CT report was 80% (75% to 86%), with a negative predictive value of 65% (58% to 72%). A significant proportion of patients being investigated for malignant disease will have malignancy despite a negative CT report. The use of CT alone in determining which patients should have invasive pleural biopsies should be re-evaluated, and further studies to define the diagnostic pathway are now required.